Strategi Mendengarkan dalam Komunikasi Manajerial - Andre Hardjana (Jurnal InterAct, 2013)
People seem to be more powerfully driven to talk than to listen. Listening rather than talking is a major concept in managerial communication. In accomplishing his/her job, a manager is expected to develop his/her listening skill more than his/her speaking skill. By building good listening habits and exercising active listening, he/she can improve communication effectiveness and raise subordinates‘ self-respect and efficacy as well.  In fact, the person can also become a pioneer of listening climate  practice  in  the  organization.  This  article  is  a  critical review of the literature related to the nature, significance, and performance of effective and active listening in managerial communication.